Narrating the anguish of being vegan in a non-vegan world - Fernanda Passos da Trindade Jorge Neres (Fórum Linguístico)
The autobiographical narrative of the anguish and pain of being vegan in a non-vegan world, similarly to other painful situations, can be characterized by some discursive specificities due to the influence of strong contextual emotions involved. Based on the theoretical concepts of hardening and narrative loop (Vasconcelos, 2022) the objective of this article is to describe and analyze these discursive specificities through a case study of an autobiographical narrative of the anguish of being vegan in a non-vegan world – vystopia. The awakening to veganism is characterized as the participant´s port of passage creating the boundaries between the before and the after in her life.  While pouring out her feelings she become capable of comprehending her experience and her capacity of surviving and learning lessons from the pain. The construction of the narrative positioning also counts with several elements such as circumstantiality, value, aspectuality, and repetition.